On the System in Bretton Woods - Williamson, John (American Economic Review, 1985)
It has become customary to look back with nostalgia at the golden age when the Bretton Woods system held sway, from the early 1950's to around 1970. It also seems to be the conventional wisdom, however, that the rules of Bretton Woods contributed little to the impressive performance of the world economy over that period-a performance characterized not merely by the fastest and most widely distributed growth in history, but also by notable stability, including near price stability except at the beginning and end of the period. The deterioration in the performance of the world economy since the early 1970's is viewed as a coincidence, or a response to common causes, rather than as a consequence of the breakdown of Bretton Woods. My purpose in selecting the title to this session was to induce critical scrutiny of these conventional attitudes. My own contribution to this task will start by describing what I conceive to have been the three essential rules of the Bretton Woods system. I shall proceed to examine the logic of those three rules in terms of recent contributions to the literature, in particular the emergent literature on policy coordination, and of recent historical experience.